Change in suspect's memory as a result of deception - Colwell, K.; Hiscock-Anisman, C.; Corbett, L.; Memon, A.; Hauselt, W.J.; Bonilla, Y. (American Journal of Forensic Psychology, 2011)
One hundred and eight participants either stole or replaced a stolen exam key from a professor's office. Half of the participants were instructed to respond honestly and to help with an investigation; the other half were instructed to distort their statement so they were not implicated. Participants did not know whether they would be asked to lie or report honestly during their time in the professor's office. After completing the task, participants again met with a research assistant, who instructed them whether to lie or respond honestly at a one-week follow-up. After the interview, participants completed a Likert-type post-event questionnaire. Deceivers reported significantly more anxiety and motivation not to get caught while in the office, even though there were no differences in the instructions given to the two groups until after participants left the office. Therefore, the act of deception changed their memory for their time in the office. This is important theoretically because it suggests that forming a lie script could be akin to other memories for counterfactual thinking. Practically, it is important to note that a deceptive perpetrator or detainee may never be able to actually provide an accurate account. Copyright 2011 American Journal of Forensic Psychology.
Keywords: anxiety; article; deception; dept.psy; female; follow up; honesty; human; human experiment; male; memory; motivation; normal human; offender; questionnaire; task performance; theft; thinking; ⛔ No DOI found

The role of conflict in continuity and change: life events associated with identity development in racially and ethnically diverse women - Anthis, Kristine (Identity, 2011)
In this archival study, life events were identified that served as precursors to identity transitions in 149 European American, African American, Mexican American, and Puerto Rican women. The data were collected during a period from the late 1970s to the early 1980s in the United States. Participants were interviewed and asked to describe events that had influenced their understanding of themselves. Events were coded into relational, career, education, personal, health-related, and miscellaneous categories. Results indicated that women were more likely to report life events regarding their relationships than events in other categories. A reexamination of the data revealed that that there were more similarities than differences among the racial and ethnic groups in terms of the life events described. Respondents were more likely to report continuity than change in their identities in response to life events serving as possible precursors to change. Results also revealed that when change did occur, it was associated with high levels of conflict particularly for the domains of relationships and educational achievement expectations. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy

Positive emotions, emotional intelligence, and successful experiential learning - Abe, Jo Ann A. (Personality and Individual Differences, 2011)
This study explored the role that positive emotions and emotional intelligence play in experiential learning. Students' field practicum journals were analyzed using the Linguistic Inquiry and Word Count Program (LIWC) and a measure of emotional intelligence was obtained using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Positive emotion words were robustly associated with almost all dimensions of supervisors' ratings of students' performance, but showed weak associations with students' ratings of perceived benefits associated with their practicum experiences. Overall El scores were correlated with several of the supervisor rating items and the Facilitating Thought and Managing Emotions subscales of the El were robustly correlated with many of the student rating items. This study thus yielded a more differentiated view of the role of positive emotions and emotional intelligence in adaptive functioning and underscored the importance of using multiple informants to assess a complex construct such as successful experiential learning. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Emotional intelligence; Experiential learning; LIWC; MSCEIT; Positive emotions; dept.psy

Functional activation for imitation of seen and heard speech - Irwin, Julia R.; Frost, Stephen J.; Mencl, W. Einar; Chen, Helen; Fowler, Carol A. (Journal of Neurolinguistics, 2011)
This study examined fMRI activation when perceivers either passively observed or observed and imitated matched or mismatched audiovisual (”McGurk”) speech stimuli. Greater activation was observed in the inferior frontal gyrus (IFG) overall for imitation than for perception of audiovisual speech and for imitation of the McGurk-type mismatched stimuli than matched audiovisual stimuli. This unique activation in the IFG during imitation of incongruent audiovisual speech may reflect activation associated with direct matching of incongruent auditory and visual stimuli or conflict between category responses. This study provides novel data about the underlying neurobiology of imitation and integration of AV speech. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Audiovisual; FMRI; Imitation; McGurk effect; Speech perception; Speech production; adult; article; auditory stimulation; brain function; brain region; controlled study; dept.psy; female; functional magnetic resonance imaging; human; human experiment; inferior frontal gyrus; male; priority journal; speech discrimination; speech perception; superior temporal gyrus; task performance; visual stimulation

Effects of neurofibromatosis type 1 on children's development - Haynes, Norris M.; Kirwan, Jacqueline R.; McCrohan, Kelly (Social Work in Public Health, 2011)
In-depth study of the human genome holds the potential to provide needed focus on genetic disorders that affect hundreds of thousands of children and significantly affect their development. Neurofibromatosis Type-1 (NF-1) is one of the most common genetic disorders that affect neurological, cognitive, social, and physical development. NF-1 affects all racial groups and both genders equally. NF-1 occurs in about 1 in 2,500 to 3,300 individuals in the population. The incidence rate at birth is about 0.0004 births in the United States and is growing in prevalence. Children with NF-1 experience a range of psychomotor and cognitive impairments that affect the quality of their social lives and their learning and academic achievements. Interventions to address the psychosocial and educational needs of children with NF-1 include a range of social and academic support services, which are most effective when they are comprehensive, involve a multidisciplinary team of educational and health experts, and include a focus on supporting and empowering family members to be effective caregivers. Efforts to address the needs of children with NF-1 and to provide adequate support to their families have significant policy implications for local, state, and federal officials.
Keywords: *Child Development; *Genome, Human; *Neurofibromatosis 1/px [Psychology]; *School Health Services; Adolescent; Adult; Aged; Child; Child Development; Child Welfare; Child, Preschool; Emotions; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Middle Aged; Neurofibromatosis; Neurofibromatosis 1; Neurofibromatosis 1/di [Diagnosis]; Neurofibromatosis 1/ep [Epidemiology]; Neurofibromatosis 1/ge [Genetics]; Patient Education as Topic; Power (Psychology); Power, Psychological; Prevalence; Risk Factors; School Health Services; Social Change; Social Work; United States; United States/ep [Epidemiology]; Young Adult; adolescent; adult; aged; article; behavior; birth rate; child; child development; child health; child welfare; cognition; dept.psy; disease incidence; disease prevalence; emotion; family empowerment; female; genetics; genome; heritability; human; human genome; infant; male; mental health; middle aged; neurofibromatosis; newborn; patient education; peer-reviewed; preschool child; prevalence; psychological aspect; psychology; risk factor; school health service; school psychologists; school-based interventions; social and emotional development; social change; social policy; social work

Augmenting acid with affective details to assess credibility - Ansarra, Ryan; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hines, Amber; Fleck, Roland; Cole, Lindsey; Belarde, Delyana (European Journal of Psychology Applied to Legal Context, 2011)
There is a need within the criminal justice systems of many countries to create a valid and applicable system of investigative interviewing and credibility assessment. The present study assesses the general validity one such system, called Assessment Criteria Indicative of Deception (ACID). ACID comprises interviewing strategies that facilitate the detection of deception and content criteria that highlight differences in verbal behavior. Sixty university undergraduates performed a staged theft under time pressure and with incentives designed to increase external validity. The participants were interviewed and assessed using the ACID procedure. Half of them were instructed to answer honestly and the other half to deny his/her participation in the theft. Results showed that honest statements were longer, more vividly detailed, and more spontaneously structured than deceptive statements. Also, the addition of affective details as a dependent measure significantly improved the ACID system. Overall, 48 of 60 statements were accurately classified (26 of 30 honest statements and 22 of 30 deceptive statements). The ACID procedure was effective and benefited from the addition of affective details. The strengths and weaknesses of this study are discussed in light of basic research into deception and potential forensic application.
Keywords: Content analysis; Credibility assessment; Detecting deception; Investigative interviewing; Testimony; dept.psy; ⛔ No DOI found

Changes in alan greenspan's language use across the economic cycle: A text analysis of his testimonies and speeches - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2011)
This study examined changes in Alan Greenspan's language use across the economic cycle by analyzing his testimonies and speeches using the Linguistic Inquiry and Word Count Program (LIWC), which is a widely used text analysis program. Consistent with expectations, Greenspan showed an increase in the composite measure of psychological distancing as well as a decline in the measure of cognitive complexity between the economic expansion and downturn periods. Interestingly, these patterns of changes became more pronounced during the purported economic recovery period. In contrast to the measures of psychological distancing and cognitive complexity, the measure of emotionality remained relatively stable across the economic cycle.
Keywords: Greenspan; LIWC; cognitive complexity; computerized text analysis; dept.psy; peer-reviewed; psychological distancing

Effect of night smoking, sleep disturbance, and their co-occurrence on smoking outcomes - Peters, Erica N.; Fucito, Lisa M.; Novosad, Claire; Toll, Benjamin A.; O'Malley, Stephanie S. (Psychology of Addictive Behaviors, 2011)
Recent evidence suggests that smoking during the night is an indicator of nicotine dependence and predicts smoking cessation failure. Night smokers are likely to experience disturbance to their sleep cycle when they wake to smoke, but we are not aware of the prevalence of night smokers' self-reported sleep disturbance. Because sleep disturbance also predicts smoking cessation failure, we examined how the pre-cessation risk factors of night smoking and sleep disturbance, and their co-occurrence, predict smoking cessation failure in a 6-week double-blind randomized controlled trial examining whether naltrexone augments the efficacy of the nicotine patch (O'Malley et al., 2006). Smokers (N = 385) completed the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and a single item of waking at night to smoke pre-cessation. Smoking status was determined at weeks 1, 6, 24, and 48 weeks after quitting. The two main findings were: (a) night smokers reported significantly greater sleep disturbance than nonnight smokers; and (b) smokers with co-occurring night smoking and sleep disturbance experienced significantly greater risk for smoking than smokers with neither risk factor. Results suggest that individuals who both wake during the night to smoke and report clinically-significant sleep disturbance represent a high-risk group of smokers. Future smoking cessation treatment might incorporate strategies related to managing these smokers' sleep habits and physiological dependence on nicotine in order to bolster their cessation outcomes.
Keywords: Adult; Double-Blind Method; Female; Humans; Male; Middle Aged; Night smoking; Outcome predictors; Pittsburgh Sleep Quality Index; Prevalence; Self Report; Sleep Disorders; Sleep disturbance; Smoking; Smoking Cessation; Smoking cessation; Tobacco Use Disorder; Treatment Outcome; adult; article; cigarette smoking; comorbidity; controlled study; dept.psy; double blind procedure; drug dose comparison; female; high risk patient; human; major clinical study; male; naltrexone; named inventories, questionnaires and rating scales; nicotine patch; night; placebo; prediction; randomized controlled trial; risk factor; sleep disorder; smoking cessation; smoking habit; tobacco dependence; treatment failure; wakefulness

AVSP - Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T.; Kroos, Christian; Irwin, Julia (2011)
Keywords: dept.psy

Effects of time between trials on rats' and pigeons' choices with probabilistic delayed reinforcers. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2011)
Parallel experiments with rats and pigeons examined reasons for previous findings that in choices with probabilistic delayed reinforcers, rats' choices were affected by the time between trials whereas pigeons' choices were not. In both experiments, the animals chose between a standard alternative and an adjusting alternative. A choice of the standard alternative led to a short delay (1 s or 3 s), and then food might or might not be delivered. If food was not delivered, there was an "interlink interval," and then the animal was forced to continue to select the standard alternative until food was delivered. A choice of the adjusting alternative always led to food after a delay that was systematically increased and decreased over trials to estimate an indifference point--a delay at which the two alternatives were chosen about equally often. Under these conditions, the indifference points for both rats and pigeons increased as the interlink interval increased from 0 s to 20 s, indicating decreased preference for the probabilistic reinforcer with longer time between trials. The indifference points from both rats and pigeons were well described by the hyperbolic-decay model. In the last phase of each experiment, the animals were not forced to continue selecting the standard alternative if food was not delivered. Under these conditions, rats' choices were affected by the time between trials whereas pigeons' choices were not, replicating results of previous studies. The differences between the behavior of rats and pigeons appears to be the result of procedural details, not a fundamental difference in how these two species make choices with probabilistic delayed reinforcers.
Keywords: *Choice Behavior; *Memory, Short-Term; *Probability Learning; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Memory, Short-Term; Motivation; Probability Learning; Psychomotor Performance; Rats; Rats, Long-Evans; Reinforcement Schedule; Species Specificity; Time Perception; animal; article; decision making; dept.psy; instrumental conditioning; learning; male; motivation; peer-reviewed; pigeons and doves; psychomotor performance; rat; reinforcement; short term memory; species difference; time perception

Is it the clicker, or is it the question? Untangling the effects of student response system use - Anthis, Kristine (Teaching of Psychology, 2011)
Previous research on the effectiveness of clickers has found their use to be positively associated with exam scores but not without methodological issues that hinder the conclusions that can be drawn. To address these limitations, the current studies isolated the effects of clickers from the effects of questions presented with clickers. Study 1 showed that students who did not use clickers to respond to questions but raised their hands performed better on exams than students who saw the same questions and responded with clickers. Study 2 found no relationship between clicker use and exam scores, which suggests that prior research claims about the effectiveness of clickers may have been premature given that clicker use was confounded with question use in those studies. Suggestions for future research are also provided.
Keywords: SRS; clickers; dept.psy; metacognition

Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T; Kroos, Christian; Irwin, Julia (Proceedings of the International Conference on Audio-Visual Speech Processing (AVSP2011), Aug 31 - Sep 3, 2011, Volterra, Italy, 2011)
Keywords: dept.psy; ⛔ No DOI found

Assessing feigned cognitive impairment in defendants hospitalized for competency restoration: further validation of the TOMI - Colwell, Lori H.; Colwell, Kevin (Journal of Forensic Psychology Practice, 2011)
Valid screens for feigned cognitive impairment are a fundamental component of any forensic assessment. The TOMI is a verbally administered, two-alternative forced-choice screen for feigned cognitive impairment in competence to stand trial (CST) evaluations. The present study provided further validation for the use of this tool in a sample of 82 forensic inpatients, the second investigation of the TOMI in a real-world, psycholegal context. Using three independent external criteria-the Test of Memory Malingering (TOMM) Trial 2 score, TOMM Retention Trial score, and a clinical treatment team decision-and these combined criteria-the Legal Knowledge scale (TOMI-L) evidenced high levels of sensitivity and specificity and excellent negative predictive power (NPP). The General Knowledge scale (TOMI-G) demonstrated poor sensitivity but high specificity and NPP. The authors discuss the utility of both scales in guiding and streamlining more thorough assessments of response styles in CST evaluations.
Keywords: Competency; Forensic assessment; Legal Knowledge scale; Malingering; Test of Malingered Incompetence; Twoalternative forced-choice; adult; analytic method; article; clinical assessment tool; clinical decision making; clinical treatment team decision; cognitive defect; competence; dept.psy; forensic medicine; human; legal aspect; major clinical study; male; psychological aspect; sensitivity and specificity; validation process

Can children with autism spectrum disorders “Hear” a speaking face? - Irwin, Julia; Tornatore, Lauren A; Brancazio, Lawrence; Whalen, D H (Child Development, 2011)
This study used eye-tracking methodology to assess audiovisual speech perception in 26 children ranging in age from 5 to 15 years, half with autism spectrum disorders (ASD) and half with typical development. Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual, and audiovisual speech perception tasks. Even when fixated on the face of the speaker, children with ASD were less visually influenced than typical development controls. This indicates fundamental differences in the processing of audiovisual speech in children with ASD, which may contribute to their language and communication impairments.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Female; Humans; Language Development Disorders; Lipreading; Male; Pattern Recognition, Visual; Perceptual Masking; Reference Values; Speech Perception; Verbal Behavior; adolescent; article; autism; child; dept.hls; dept.psy; female; human; interpersonal communication; language disability; lip reading; male; pattern recognition; perception; preschool child; psychological aspect; reference value; speech perception; verbal behavior

Effects of playing wii on well-being in the elderly: physical activity, loneliness, and mood - Kahlbaugh, Patricia E; Sperandio, Amanda J; Carlson, Ashley L; Hauselt, Jerry (Activities, Adaptation & Aging, 2011)
Effects of compensatory strategies offered by Wii technology on physical activity, loneliness, and mood are investigated. Thirty-five individuals (M = 82 years) were randomly assigned to either playing Wii or watching television with a partner for 10 weeks. Physical activity, loneliness, mood, life satisfaction, and health were assessed. The elderly playing Wii had lower loneliness and a pattern of greater positive mood compared to the television group. No differences in life satisfaction or physical activity were found, but loneliness predicted positive mood, and positive mood predicted physical activity. This investigation points to the benefits of using Wii for well-being, particularly social connection and enjoyment. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy; integrative game playing; loneliness; mood; older adult recreation; well-being